The historical exercise as an exercise of power: the Cabinet des chartes and the psychogenesis of French archiving. - Domínguez, David J. (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This work has the objective of carrying out a critical review of the historical-scholarly activity of the Cabinet des chartes. Created in the mid-18th century, this institution represents a clear example of osmosis between politics and historical learning. In a context marked by the dispute between the monarchy and the parliaments, the study of the Cabinet des chartes represents a strategic access point to the field of historiographic reflection, which in turn allows us to illustrate the way in which the research activity is contingent on the creation of a unified body of law, itself the result of a compilation of documents conducted by this institution. This article puts forward an analysis of the lines of investigation and the ideological concerns of the Cabinet. For this, it is necessary to carry out a critical analysis of the documental sources found throughout this activity, making special emphasis on those aspects that indicate the struggle of the monarchical institution for the accumulation of symbolic capital. Finally, the text reflects upon the imprint that this archivistic activity has left for the classificatory frameworks of French historiography of the late 19th century.